Inflation, proton decay, and Higgs-portal dark matter in $$SO(10) × U(1)_ψ $$ SO(10)×U(1)ψ - Nobuchika Okada; Digesh Raut; Qaisar Shafi (European Physical Journal C: Particles and Fields, 2019)
Abstract We propose a simple non-supersymmetric grand unified theory (GUT) based on the gauge group $$SO(10) × U(1)_ψ $$ SO(10)×U(1)ψ . The model includes 3 generations of fermions in $$16$$ 16 ($$+1$$ +1 ), $$10$$ 10 ($$-2$$ -2 ) and $$1$$ 1 ($$+4$$ +4 ) representations. The $$16$$ 16 -plets contain Standard Model (SM) fermions plus right-handed neutrinos, and the $$10$$ 10 -plet and the singlet fermions are introduced to make the model anomaly-free. Gauge coupling unification at $$M_{GUT} \simeq 5 × 10^{15}{-}10^{16}$$ MGUT≃5×1015-1016 GeV is achieved by including an intermediate Pati–Salam breaking at $$M_{I} \simeq 10^{12}{-}10^{11}$$ MI≃1012-1011 GeV, which is a natural scale for the seesaw mechanism. For $$M_{I} \simeq 10^{12}{-}10^{11}$$ MI≃1012-1011 , proton decay will be tested by the Hyper-Kamiokande experiment. The extra fermions acquire their masses from $$U(1)_ψ $$ U(1)ψ symmetry breaking, and a $$U(1)_ψ $$ U(1)ψ Higgs field drives a successful inflection-point inflation with a low Hubble parameter during inflation, $$H_{inf} \ll M_{I}$$ Hinf≪MI . Hence, cosmologically dangerous monopoles produced from SO(10) and PS breakings are diluted away. This is the first SO(10) model we are aware of in which relatively light intermediate mass ($$\sim 10^{10}{-}10^{12}$$ ∼1010-1012 GeV) primordial monopoles can be adequately suppressed. The reheating temperature after inflation can be high enough for successful leptogenesis. With the Higgs field contents of our model, a $$Z_2$$ Z2 symmetry remains unbroken after GUT symmetry breaking, and the lightest mass eigenstate among linear combinations of the $$10$$ 10 -plet and the singlet fermions serves as a Higgs-portal dark matter (DM). We identify the parameter regions to reproduce the observed DM relic density while satisfying the current constraint from the direct DM detection experiments. The present allowed region will be fully covered by the future direct detection experiments such as LUX-ZEPLIN DM experiment. In the presence of the extra fermions, the SM Higgs potential is stabilized up to $$M_{I}$$ MI .